2019
DOI: 10.1016/j.indcrop.2018.10.055
|View full text |Cite
|
Sign up to set email alerts
|

All-cellulose composites from alfa and wood fibers

Abstract: All-cellulose composites (ACCs) in which both matrices and reinforcing fibers are made from lignocellulose were successfully obtained from alfa (Stipa tenacissima L) and wood (Genus Betula) fibers. Matrices were prepared either from alfa or wood pulps that were dissolved in 8 wt% NaOH-water, while reinforcing fibers were alfa in both matrices. Prior to the dissolution, alfa and wood pulps were acid hydrolyzed in order to decrease cellulose degree of polymerization to 149 and 145, respectively. The degree of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 22 publications
1
27
0
3
Order By: Relevance
“…Porosity can be roughly estimated from the ratio of composite bulk to skeletal density, with the latter taken as 1.5 g/cm 3 . Porous composites with even lower densities, around 0.5 -1.0 g/cm 3 , were reported for allcellulose composites made from alfa fibers (Labidi et al 2019) and by impregnating pulp sheets with NaOH-urea-water (Piltonen et al 2016;Hildebrandt et al 2017). The reinforcement content plays the major role in the density of composites, and the DP of dissolved pulp has a minor effect (Figure 4).…”
Section: Morphology and Properties Of All-cellulose Compositesmentioning
confidence: 93%
See 2 more Smart Citations
“…Porosity can be roughly estimated from the ratio of composite bulk to skeletal density, with the latter taken as 1.5 g/cm 3 . Porous composites with even lower densities, around 0.5 -1.0 g/cm 3 , were reported for allcellulose composites made from alfa fibers (Labidi et al 2019) and by impregnating pulp sheets with NaOH-urea-water (Piltonen et al 2016;Hildebrandt et al 2017). The reinforcement content plays the major role in the density of composites, and the DP of dissolved pulp has a minor effect (Figure 4).…”
Section: Morphology and Properties Of All-cellulose Compositesmentioning
confidence: 93%
“…The "short-fiber" all-cellulose composites can be produced via cellulose incomplete dissolution (many studies use microcrystalline cellulose) (Gindl and Keckes 2005;Duchemin et al 2009; Abbot and Bismarck 2010) or through fiber dispersion in cellulose solution (Ouajai and Shanks 2009;Yang et al 2010;Nadhan et al 2012;Labidi et al 2019). The latter mimics the production of conventional short-fiber polymer composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second production pathway of all-cellulose composites presented in Figure 3.6 is based on randomly dispersed short fibers. Two approaches can be identified; the first one is based on partial dissolution of short fibers in a solvent (similarly to the pathway 1) (Gindl & Keckes 2005;Duchemin et al 2009a;Abbot & Bismarck 2010) and in the second approach the short fibers are dispersed in cellulose solution (Ouajai & Shanks 2009;Yang et al 2010;Nadhan et al 2012;Labidi et al 2019). The benefit of the latter approach is that it mimics the production of conventional short fiber polymer composites.…”
Section: All-cellulose Compositesmentioning
confidence: 99%
“…Numerous non-destructive methods as X-ray diffraction (XRD) 10,12,13 , attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) spectroscopy 14,15 , Raman spectroscopy 10 , solid-state 13 C nuclear magnetic resonance (NMR 13 C/CP-MAS) measurements 10 , and differential scanning calorimetry (DSC) 13 , were employed in several works to quantify the cellulose crystallinity and understand the structural roles of cellulose in the recalcitrant, mechanical and biological properties of plant cell walls. Lionetto et al 15 , using X-ray diffraction and FTIR spectroscopy to quantify crystalline cellulose in lignocellulosic biomass, revealed that the crystallinity index (Cr.I.)…”
Section: Introductionmentioning
confidence: 99%